Satisfaction and Occupational Performance in Patients with Functional Movement Disorder - Sarah E. Dahlhauser; Amanda Theuer (Scholarworks @ WMU, 2017)
Background: Behavioral Shaping Therapy (BeST) is a program that uses a multidisciplinary approach to treat patients diagnosed with functional movement disorder (FMD). While this diagnosis is classified as a psychological disorder by the Diagnostic and Statistical Manual of Mental Disorders, the BeST program focuses on treating the physical manifestations of FMD. Occupational therapists are an integral part of the multidisciplinary team, employing a variety of cognitive behavioral and motor reprogramming techniques to normalize movement patterns. Method: Patients 18 years of age or older with a confirmed diagnosis of FMD participated in this study. This retrospective chart review used the Canadian Occupation Performance Measure to examine the patients' satisfaction and perceived change in task performance on discharge from the program. Results: Results from the dependent t-test indicated a positive outcome after participating in the BeST program, with a mean change in performance of 3.4 and a mean change in satisfaction of 4.7. Discussion: This study shows that occupational therapy can have a positive effect on patients diagnosed with FMD.